Analisis Sumber Daya Manusia Melalui Kebijakan Mutasi Di Sekolah Dasar - Wahyu Susiloningsih; Rarasaning Satianingsih; Tasya Maulidia (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this review study is to show how mutations support the expansion of human resources (teachers). Mutation is a policy taken by the government to equalize HR (teacher) competence in an area. The method used in this article is a review of the literature used to write this research. The search for relevant publications was conducted using Google Scholar and websites of relevant journals and books. Therefore, this study tries to synthesize information from previous research which then concludes that mutation policies can develop HR (teachers) regarding the evolution of human resources (HR).